Hexane isomers sorption on the rigid framework MOF MIL-100(Cr) - Mendes, Patricia (2013)
In this work we studied the hexane isomers sorption on the MIL-100(Cr) [1]. The first part of the study was related to the pattern MIL-100(Cr) solid, the second dealt with the MIL-100(Cr) grafted with EtAp (Ethylamine pure) and the third with MIL-100(Cr)MEDA (Methyl ethylene diamine). The synthesis and characterization of MIL-100 (Cr), MIL-100(Cr)EtAp and MIL-100(Cr)MEDA was performed at Institut Lavoisier de Versailles. The separation and adsorption capacity of each MOF were evaluated through breakthrough experiments in a chromatographic system at LSRE using an equimolar mixture of four hexane isomers: n-hexane (nHEX) (RON 25), 3-methylpentane (3MP) (RON 75), 2,3-dimethylbutane (23DMB) (RON 103) and 2,2-dimethylbutane (22DMB) (RON 94) with the objective to the develop an adsorptive process to separate hexane isomers (kinetic diameter very similar) in order to improve the quality of gasoline measured by the octane number (RON).